Human Resources Planning Using Workload and Job Analysis as The Basis of Improving the Organizational Structure in The Marketing (Case Study of Pt. IMST) - Ni Gusti Made Rai; Amanullah Baihaqi; Prahardika Prihananto; Syarifa Hanoum (Institut Teknologi Sepuluh Nopember, 2023)
Strategic planning is crucial for every company to achieve organizational goals, with a focus on effectiveness, efficiency, and productivity in human resource management. Human resource planning involves analyzing workloads in alignment with job descriptions for each position. This research was carried out within PT IMST's Marketing Division, a company operating in the railroad component distribution and trading industry. The primary objective was to examine employee workloads and integrate the findings with job analysis to inform human resource planning. The study revealed that increased market penetration and project demand have led to higher physical and mental workloads for workers. The NASA TLX method was employed to conduct the workload analysis. Based on the research results, it is recommended that the optimal number of personnel be five for each position of Head and Junior Specialist, four for Project Achievement Staff I, three for Project Achievement Staff II, and six for Administrative Staff. To address these staffing needs, human resource planning should prioritize recruiting or adding personnel who possess the requisite qualifications and competencies in accordance with the established positions. By aligning recruitment efforts with the workload analysis and job descriptions, the company can ensure that its workforce is appropriately sized and equipped to efficiently meet market demands and achieve organizational success